3D-printed copper-containing tailored titanium alloys with corrosion resistance, biocompatibility, and anti-inflammatory properties for enhanced guided bone regeneration - Lan Luo; Lan Luo; Quan Zhong; Quan Zhong; Zi-Qin Chen; Zi-Qin Chen; Xiao-Hong Wu; Xiao-Hong Wu; Shu-Man Li; Zhen-Zhu Xue; Zhen-Zhu Xue; Yan-Jin Lu; et al. (Frontiers in Bioengineering and Biotechnology)
IntroductionGuided bone regeneration (GBR) serves as a critical technique in dental implantology, relying heavily on barrier membranes for successful alveolar bone augmentation. Titanium mesh, widely utilized in GBR procedures, faces a high exposure rate that leads to infections and compromised clinical outcomes. While 3D-printed personalized meshes have reduced exposure rates, infection risks persist, necessitating the development of bioactive solutions.MethodsIn this study, selective laser melting (SLM) was employed to fabricate copper-bearing titanium meshes using Ti-xCu powders (x=0, 4, 6, 8 wt%). This investigation systematically evaluated the effects of copper content on corrosion resistance, biocompatibility, osteogenic potential, and anti-inflammatory properties of the Ti-xCu alloys.ResultsMicrostructural analysis revealed that increasing copper content enhanced Ti2Cu precipitation within the α-Ti matrix. While increased copper content did not compromise corrosion resistance, it resulted in higher copper ion release concentrations. Antibacterial assays demonstrated that alloys with copper content exceeding 4 wt% exhibited >90% bacterial reduction against S. aureus and E. coli. In vitro studies showed that Ti-6Cu optimally promoted osteoblast proliferation and upregulated osteogenic genes (Alp, Col-1). Furthermore, Ti-6Cu upregulated anti-inflammatory factors (Il-10, Arg-1) while downregulating inflammatory factors (Tnf-α, Il-6).ConclusionThe study established SLM-treated antibacterial Ti-6Cu alloy exhibited favorable biological activity, demonstrating promising potential for application in regeneration scaffolds.